Biodegradable celastrol-loaded albumin nanoparticles ameliorate inflammation and lipid accumulation in diet-induced obese mice. (12th January 2022) - Fan, Ni; Zhao, Jia; Zhao, Wei; Shen, Yanting; Song, Qingchun; Shum, Ho Cheung; Wang, Yu; Rong, Jianhui
Abstract : Biocompatible celastrol-loaded bovine serum albumin nanoparticles effectively ameliorated inflammation and lipid accumulation in diet-induced obese mice. Abstract : Obesity is hallmarked by endoplasmic reticulum (ER) stress, chronic inflammation and metabolic dysfunctions. The control of obesity is the key to preventing the onset of non-alcoholic fatty liver disease, diabetes, cerebro-cardiovascular diseases and cancers. As a promising anti-obesity drug, plant-derived celastrol is challenged by poor water solubility and low oral bioavailability in clinical applications. The present study was designed to develop a biocompatible albumin-based nanoparticle carrier system for the controlled release of celastrol in diet-induced obese mice. Celastrol was loaded into bovine serum albumin (BSA) nanoparticles to yield celastrol-BSA-NPs by high pressure homogenization. Celastrol-BSA-NPs exhibited spherical morphology, narrow size distribution with a diameter of 125.6 ± 2.2 nm, satisfactory drug-loading efficiency at 13.88 ± 0.12% and a sustained-release profile over a period of 168 h. Compared with free celastrol, celastrol-BSA-NPs effectively improved cellular uptake, intestinal absorption and hepatic deposition. In animal experiments, celastrol-BSA-NPs outperformed free celastrol in lowering lipid accumulation, improving insulin sensitivity, and reducing inflammation in diet-induced obesity. Collectively, celastrol-BSA-NPs exhibited better bioavailability and in vivo efficacy in the treatment of diet-induced obesity. Importantly, such albumin-based nanoparticles may be a general biocompatible drug carrier system for the controlled release of hydrophobic compounds ( e.g., celastrol) for the treatment of obesity and non-alcoholic fatty liver disease.